ESG REPORTING AND MARKET CAPITALIZATION IN ASIA: THE ROLE OF NATIONAL CULTURAL VALUES - Syahputri, Anggelia; Asyitiyani, Mirza Khayhan; Nurmayanti, Risda (Jurnal Akuntansi dan Keuangan Indonesia, 2025)
Background: The discussion around sustainability issues is advancing in Asia, highlighting ESG disclosure as a critical competitive advantage for companies. Corporate ESG disclosure can influence investment decisions as investors seek information on companies' ESG practices. Method: This study examines the impact of ESG reporting on market capitalization and the moderating role of Hofstede's cultural values. The analysis is based on panel data from listed firms in nine Asian countries (Indonesia, Malaysia, Thailand, the Philippines, Singapore, India, Taiwan, Japan, and China) over the period 2018–2023. Findings: The findings show a positive relationship between cumulative ESG scores and market capitalization in both developed and developing markets. Individualism, long-term orientation, uncertainty avoidance, and masculinity positively moderate this relationship, while power distance moderates it negatively. The moderating effect of cultural values is found to be weaker in developing markets. Conclusion: This study contributes to the literature by emphasizing the impact of ESG disclosure on market performance in Asian contexts. It offers insights for regulators in designing strategies to enhance economic stability through improved corporate market capitalization. Novelty/Originality of this article: It also addresses the limited literature on the relationship between ESG and market capitalization in Asian markets, contrasting with most studies focused on Europe.